Association between uric acid and the risk of hemorrhagic transformation in patients with acute ischemic stroke: a systematic review and meta-analysis - Ying Qian; Ying Qian; Na Li; Yuanyuan Li; Chenxi Tao; Zhenhong Liu; Zhenhong Liu; Guoxia Zhang; Fan Yang; Hongrui Zhang; Hongrui Zhang; Yonghong Gao; et al. (Frontiers in Neurology, 2024)
BackgroundThe relationship between hemorrhagic transformation (HT) and uric acid (UA) remains controversial. This study aimed to investigate the relationship between UA concentrations and the risk of HT following acute ischemic stroke (AIS).MethodsElectronic databases were searched for studies on HT and UA from inception to October 31, 2023. Two researchers independently reviewed the studies for inclusion. STATA Software 16.0 was used to compute the standardized mean difference (SMD) and 95% confidence interval (CI) for the pooled and post-outlier outcomes. Heterogeneity was evaluated using the I2 statistic and the Galbraith plot. Additionally, sensitivity analysis was performed. Lastly, Begg’s funnel plot and Egger’s test were used to assess publication bias.ResultsA total of 11 studies involving 4,608 patients were included in the meta-analysis. The pooled SMD forest plot (SMD = −0.313, 95% CI = −0.586–−0.039, p = 0.025) displayed that low UA concentrations were linked to a higher risk of HT in post-AIS patients. However, heterogeneity (I2 = 89.8%, p < 0.001) was high among the studies. Six papers fell outside the Galbraith plot regression line, and there exclusive resulted in the absence of heterogeneity (I2 = 52.1%, p = 0.080). Meanwhile, repeated SMD analysis (SMD = −0.517, 95% CI = −0.748–−0.285, p = 0.000) demonstrated that the HT group had lower UA concentrations. Finally, Begg’s funnel plot and Egger’s test indicated the absence of publication bias in our meta-analysis.ConclusionThis meta-analysis illustrated a substantial connection between UA concentrations and HT, with lower UA concentrations independently linked with a higher risk of HT post-AIS. These results lay a theoretical reference for future studies.Systematic review registration:https://www.crd.york.ac.uk/PROSPERO/CRD42023485539.